EVALUATION OF ANTI-AGING AND ANTI-ACNE EFFECT OF ANDALIMAN (ZANTHOXYLUM ACANTHOPODIUM DC.) ETHANOLIC EXTRACT PEEL OFF GEL MASK - T, Ismanelly Hanum; Laila, Lia (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was conducted to evaluate the anti-aging and anti-acne effect of and aliman ethanolic extract (AEE) in the form of peel off gel mask (PGM) on human skin. Methods: The formulation of PGM base was consisted of polyvinyl alcohol, glycerine, methylparaben, propylparaben, Carbomer 940, and distilled water (blank). The AEE (30%) was formulated in the PGM base and labeled as F1. The anti-aging and anti-acne tests were conducted by comparing the blank and the F1. The evaluation of anti-aging activity was conducted using skin analyzer apparatus. The aging parameters were moisture, evenness, pore size, black spot, and wrinkle of the skin. The anti-acne evaluation was conducted on color, shape, volume, and number of acne. The data were collected for 4 weeks. Results: The anti-aging evaluation of andaliman PGM showed that the and AEE PGM could pretend the skin moisture, skin evenness, small pore size, and declined in number of black spot and wrinkle. The anti-acne evaluation showed the healing of acne after 4 weeks treatment. Conclusion: It is concluded that and AEE PGM can be used as an effective anti-aging and anti-acne dosage form.